A Proprioceptive Janus Fiber with Controllable Multistage Segments for Bionic Soft Robots - Hao Zhu (56502) (2024)
Smart fibers capable of integrating the multifunctionality of actuation and self-sensation into a single proprioceptive device have significant applications in soft robots and biomedicine. Especially, the achievement of self-sensing the movement patterns of different actuating segments in one fiber is still a great challenge. Herein, in this study, a fiber with the controllable Janus architecture is successfully proposed via an artful centrifugation-driven hierarchical gradient self-assembly strategy, which couples two functional components of piezoresistive carbon nanotubes and magnetic NdFeB nanoparticles into the upper and lower layers of this flexible fibrous framework with the porous sponge structure partially, respectively. As predicted, the final product exhibits the as-anticipated bionic proprioceptive behaviors of programmable actuating deformation and highly selective response to bending, stretching, and pressure with high washable stability and mechanical performances. More importantly, assisted by the different three-dimensional printing molds, the superlong Janus fibers with various controllable lengths of the reversed but sequential multistage segments can be fabricated, offering the hybrid magnetic actuation and proprioceptive sensation existing at arbitrary nodes. Therefore, several kinds of soft organism-inspired Janus fiber-derived soft robots with the arbitrarily controlled segmental characters were assembled as the proof-of-concept, which can not only realize a snake or inchworm-inspired successive contracting-stretching deformation and a sperm-inspired self-rotating crawling motion but also self-sense the signals of each segment themselves in real time and then be used to navigate an object to target position in a liquid-filled confined tube. It is believed that this work promotes the further development of proprioceptive soft robots.